High‐Intensity Versus Non‐High‐Intensity Statins in Patients Achieving Low‐Density Lipoprotein Cholesterol Goal After Percutaneous Coronary Intervention. Issue 21 (6th November 2018) - Kim, Juwon; Park, Kyu Tae; Jang, Mi Ja; Park, Taek Kyu; Lee, Joo Myung; Yang, Jeong Hoon; Song, Young Bin; Choi, Seung‐Hyuk; Gwon, Hyeon‐Cheol; Lee, Sang‐Hoon; Hong, Kyung Pyo; Hahn, Joo‐Yong
Abstract : Background: Whether use of high‐intensity statins is more important than achieving low‐density lipoprotein cholesterol (LDL‐C) target remains controversial in patients with coronary artery disease. We sought to investigate the association between statin intensity and long‐term clinical outcomes in patients achieving treatment target for LDL‐C after percutaneous coronary intervention. Methods and Results: Between February 2003 and December 2014, 1746 patients who underwent percutaneous coronary intervention and achieved treatment target for LDL‐C (<70 mg/dL or >50% reduction from baseline level) were studied. We classified patients into 2 groups according to an intensity of statin prescribed after index percutaneous coronary intervention: high‐intensity statin group (atorvastatin 40 or 80 mg, and rosuvastatin 20 mg, 372 patients) and non‐high‐intensity statin group (the other statin treatment, 1374 patients). The primary outcome was a composite of cardiac death, myocardial infarction, or stroke. Difference in time‐averaged LDL‐C during follow‐up was significant, but small, between the high‐intensity statin group and non‐high‐intensity statin group (59±13 versus 61±12 mg/dL; P =0.04). At 5 years, patients receiving high‐intensity statins had a significantly lower incidence of the primary outcome than those treated with non‐high‐intensity statins (4.1% versus 9.9%; hazard ratio, 0.42; 95% confidence interval, 0.23–0.79; P <0.01). Results were consistent after propensity‐score matching (4.2% versus 11.2%; hazard ratio, 0.36; 95% confidence interval, 0.19–0.69; P <0.01) and across various subgroups. Conclusions: Among patients achieving treatment target for LDL‐C after percutaneous coronary intervention, high‐intensity statins were associated with a lower risk of major adverse cardiovascular events than non‐high‐intensity statins despite a small difference in achieved LDL‐C level.